2011
DOI: 10.1007/s11199-011-0071-9
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Women Gamblers: Gender-Related Aspects of Control

Abstract: This study examines the control exhibited by pathological women gamblers over their lives and their surroundings, and how this is governed by their perception of their gender role and socio-cultural expectations of them as women. Seventeen pathological women gamblers (13 of whom were mothers) were recruited from three addiction treatment centers in Israel, and participated in semi-structured interviews. Three central themes emerged during analysis: maintaining control over the gender roles-putting child raisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…However, this aspect has not been extensively studied in behavioral addictions. Gavriel-Fried and Ajzenstadt [ 13 ] reported that, in the case of mothers with gambling disorder, they retain control of their maternal duties while, at the same time, engaging in gambling behavior. In fact, they tended to maintain gambling behaviors since, among other aspects, their maternal role was well covered, and their responsibilities were not neglected.…”
Section: Introductionmentioning
confidence: 99%
“…However, this aspect has not been extensively studied in behavioral addictions. Gavriel-Fried and Ajzenstadt [ 13 ] reported that, in the case of mothers with gambling disorder, they retain control of their maternal duties while, at the same time, engaging in gambling behavior. In fact, they tended to maintain gambling behaviors since, among other aspects, their maternal role was well covered, and their responsibilities were not neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the 2000s, the number of qualitative investigations into gambling has grown (e.g. Li, 2007;Casey, 2008;Tepperman, 2009;Corney & Davis, 2010a, 2010bGavriel-Fried & Ajzenstadt, 2012;Reith & Dobbie, 2013). The application of qualitative methodology can be especially relevant in studies focusing on topics such as addiction, which may encompass individual, interpersonal and intergenerational distress, coping and social problem-solving.…”
Section: Introductionmentioning
confidence: 99%
“…In Israel, this role is strongly influenced by the good mother myth of women’s instinctive ability and desire to care for and to sacrifice their own needs for those of their children (Hacker, 2005). Hence, it is not surprising that Israeli pathological women gamblers emphasized the role of motherhood in their life, indicating their desire to fulfill the ideal of the good mother (Gavriel-Fried & Ajzenstadt, 2012) and drug-addicted Israeli women are subjected to harsh stigmatization by institutions and the general society (Salan, 2005). Although little is known regarding their prevalence, it is estimated that women account for 10% to 30% of the population of about 25,000–30,000 heroin addicts in Israel (Isralowitz, Reznik, Spear, Brecht, & Rawson, 2007).…”
Section: Introductionmentioning
confidence: 99%